Evaluation of different modules for the management of tomato fruit borer, Helicoverpa armigera pest of tomato (Journal of Applied and Natural Science, 2015)
Among, six modules tested against Helicoverpa armigera on tomato, the IPM module I consisting interspersing of 1 row of african marigold after every 8 rows of tomato as well as on the periphery of the plot and spray of neem based formulation gromin 1 % EC @ 0.5 ml /l on appearance of the first instar larvae.IPM module II was interspersing of 1 row of african marigold after every 8 rows of tomato as well as on the periphery of the plot spray of neem based formulation gromin 1 % EC @ 0.5 ml /l on appearance of the first instar larvae and two spray of HaNPV @ 350 LE/ha alternated with neem oil @ 0.5 % + 0.1 % soap solution.IPM module III consisting interspersing of 1 row of african marigold after every 8 rows of tomato as well as on the periphery of the plot and two spray of Beauvaria basiana @ 40g/10 l at appearance of first instar larvae alternated with Nikuchhi @ 1.0 %. and IPM module IV are growing of african marigold after every 8 rows of tomato as well as on the periphery of the plot and two spray of HaNPV @ 350 LE/ha on appearance of first instar larvae followed by spray of Decidan 32.8% EC @ 15ml/10 litre. The IPM module V was alternate spray of Polytrin c 44 % EC @ 10ml/10 litre on appearance of first instar larvae and subsequent spray at 15 days intervals and Module VI was Control. IPM-IV module was found highly effective and economical for management of tomato fruit borer, Helicoverpa armigera and it exhibited least tomato fruit borer damage (3.44%) and maximum tomato yield (257.25q/ha). This research gave the best result to farmers for the control of H. armigera in tomato crops.